A microscopic theory of the alpha-nucleus optical potential - Bonaccorso, A; Bonaccorso, Angela (1980)
A semiclassical theory of the optical potential based on Feynman's path integral formalism is proposed. The new approach gives an expression for the time integral of the optical potential in terms of the ground state to ground state transition amplitude. The transition amplitude is first calculated by perturbation theory. Then the formalism is applied to the study of the imaginary part of the optical potential for a-elastic scattering on 160 and 40Ca. The projectile is treated as a point-like particle and the target is described by the shell model. The relative motion is calculated in a semiclassical approximation. The intermediate states of the target are lp-lh states and the centre-of-mass spurious excitations are explicitly calculated. The absorption of flux from the elastic channel due only to collective excitations is evaluated by taking as intermediate states only the giant quadrupole and monopole states. The relation to phenomenological potentials is clarified by comparing time integrals along classical trajectories. In order to test the validity of perturbation theory the ground state to ground state transition amplitude is also calculated by solving a set of coupled channel equations. Time integrals of the imaginary part of the optical potential are compared with the results obtained by perturbation theory. Information about the real part of the potential is also extracted. Finally a comparison is made with other theories of the optical potential which use perturbation theory. Some final remairfcs and suggestions for future developments conclude this work.